Extension Provides Fresh Feed and Silage For Cattle in Kinali Village: Penyuluhan Menyediakan Pakan Segar dan Silase Untuk Ternak Sapi di Desa Kinali - Ezward, Chairil; Yoshi Lia Anggrayni; A.Haitami; Rahman Al Insanu; Zanuar Fatwa Ardifa; Rizki Prima; Andika Saputra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The presence of cattle in Kinali Village provides additional economic value for the community. However, cattle farming activities are still hampered by the availability of feed. Feed can be either fresh feed or silage. The purpose of this PkM program is to provide community understanding about providing cattle feed, both fresh feed and silage. The methods used include dialogue, material development, and lectures. The success of the program was measured by distributing questionnaires both before and after the extension program. The results of the extension showed an increase in public understanding of how to make silage, namely from 9.52% to 90.48% with the criteria of understanding. The importance of this extension program is to ensure the community can provide cattle feed by utilizing the potential available in Kinali Village. This extension is crucial for providing cattle feed that is sufficient in quantity, quality, continuity, and long-lasting. This activity is an effort to improve community welfare.